The TIA1 RNA-Binding Protein Family Regulates EIF2AK2-Mediated Stress Response and Cell Cycle Progression - Meyer, Cindy; Garzia, Aitor; Mazzola, Michael; Gerstberger, Stefanie; Molina, Henrik; Tuschl, Thomas (Molecular cell, 2018)
TIA1 and TIAL1 encode a family of U-rich element mRNA-binding proteins ubiquitously expressed and conserved in metazoans. Using PAR-CLIP, we determined that both proteins bind target sites with identical specificity in 3' UTRs and introns proximal to 5' as well as 3' splice sites. Double knockout (DKO) of TIA1 and TIAL1 increased target mRNA abundance proportional to the number of binding sites and also caused accumulation of aberrantly spliced mRNAs, most of which are subject to nonsense-mediated decay. Loss of PRKRA by mis-splicing triggered the activation of the double-stranded RNA (dsRNA)-activated protein kinase EIF2AK2/PKR and stress granule formation. Ectopic expression of PRKRA cDNA or knockout of EIF2AK2 in DKO cells rescued this phenotype. Perturbation of maturation and/or stability of additional targets further compromised cell cycle progression. Our study reveals the essential contributions of the TIA1 protein family to the fidelity of mRNA maturation, translation, and RNA-stress-sensing pathways in human cells.